Contamination of fresh and dried tomato by Alternaria toxins in southern Italy. Issue 5 (4th May 2019) - Sanzani, Simona Marianna; Gallone, Teresa; Garganese, Francesca; Caruso, Andrea Giovanni; Amenduni, Mario; Ippolito, Antonio
ABSTRACT: In the present investigation, fresh and dried tomato samples from markets and packinghouses located in Apulia region (southern Italy) were analysed for Alternaria toxins. All samples proved to be contaminated by tenuazonic acid (TeA); in particular, dried tomatoes were contaminated in the range 425–81, 592 µg/kg, while fresh tomatoes were in the range 11–4560 µg/kg. The second most abundant toxin was alternariol monomethyl ether (AME), followed by tentoxin (TEN) and alternariol (AOH). Overall dried tomatoes were more contaminated than fresh ones, although this seemed not directly related to the presence of sodium chloride, utilized in the drying process. Five representative Alternaria isolates within those collected from samples proved to be one Alternaria arborescens (A215) and four Alternaria alternata . Within the latter species, one strain belonged to morphotype tenuissima (A216), and three to alternata (A214, A217 and A218). They were confirmed to produce TeA, AOH, and AME in vitro . This study demonstrates the possible risk for consumers' health related to the consumption of contaminated fresh and dried tomatoes, and thus the need for suitable control strategies. Graphical abstract: